"Peace propaganda"? the application of Chomsky's propaganda model to the Daily Nation's coverage of the 2013 Kenyan elections. Issue 2 (3rd April 2017) - Maweu, Jacinta
ABSTRACT: This article uses the third and fourth filters of Herman and Chomsky's Propaganda Model, namely, official sources and flak, to examine how the Daily Nation, which is the largest circulating newspaper in Kenya, covered the 2013 Kenyan elections. In the run up to the elections, several institutions, among them the Independent Electoral and Boundaries Commission (IEBC) of Kenya and the Media Council of Kenya (MCK), organised several workshops with media owners and journalists in the name of "peace journalism" to avoid a repeat of the 2007/2008 post-election violence. Although such efforts paid off because there was no physical post-election violence, questions have been raised as to whether this extensive peace training translated to "peace propaganda" making journalists and the media in general engage in excessive self-censorship in the name of peaceful elections thereby neglecting their watchdog role. Using the findings from a qualitative content analysis of the Daily Nation as a case study and semi-structured interviews with civil society organisations as media monitors, it can be arguably observed that the Daily Nation avoided any "contentious electoral issues" for fear of flak and relied overly on the IEBC and other government agencies as official sources of critical electoral information.